Tackling unregistered employment in European regions: Towards a variegated policy approach - Colin C. Williams (UTMS Journal of Economics, 2021)
To tackle participation in unregistered employment, the conventional policy approach has been to deter such work by increasing the penalties and risk of detection. Recently, an alternative preventative approach has emerged that tackles participation in unregistered employment by improving citizens vertical trust (in the state) and horizontal trust (in each other). To evaluate these competing policy approaches across different European regions, Eurobarometer survey data collected in 2019 is analysed. The finding is that in the EU as a whole, the likelihood of participating in unregistered employment is not significantly associated with the perceived penalties and likelihood of being caught, but there is a strong significant association between the likelihood of participating in unregistered employment and the level of vertical and horizontal trust, suggesting the need to moved beyond a deterrence approach. However, one approach does not fit all European regions. A variegated approach is required. In South-East Europe, East-Central Europe and the Nordic nations, it is only horizontal trust that is significantly associated the likelihood of engaging in unregistered employment, whilst in Southern Europe it is vertical trust and the risk of detection. The implications for theory and policy are discussed.
Keywords: H26; J46; K42; O17; Z18; 330; informal economy; tax compliance; tax morale; public policy; Southern Europe